Exploring the ethnobotany of natural dye plants in Kalibawang Sub-district, Wonosobo District, Indonesia through traditional knowledge, conservation, and community empowerment - Muhammad Nur Sulton; Reginald Maghfirot Rammadhani Guzherra; ⁠Reinata Aulia Fahimah; Renanda Aristha Putri; Rossiana Indah Permatasari; SURAPON SAENSOUK; JOHAN ISKANDAR; JATNA SUPRIYATNA; Ahmad Dwi Setyawan (Smujo International, 2025)
Abstract. Sulton MN, Rammadhani RM, Fahimah RA, Putri RA, Permatasari RI, Saensouk S, Iskandar J, Supriyatna J, Setyawan AD. 2025. Exploring the ethnobotany of natural dye plants in Kalibawang Sub-district, Wonosobo District, Indonesia through traditional knowledge, conservation, and community empowerment. Nusantara Bioscience 17: 155-168. The use of synthetic dyes can cause environmental and health problems. Natural dyes can be a novelty to replace synthetic dyes because they contain materials that are more environmentally friendly, non-toxic, and sustainable. This ethnobotanical research was carried out to reveal the traditional knowledge of the people in Kalibawang Sub-district, Wonosobo District, Indonesia, regarding the use of various species of plants as a source of natural dyes. The purpose of this study is to analyze the species of plants that can produce natural colors used by the people of Kalibawang Sub-district, as well as to assess their conservation and sustainability and empower the community. The method used is an ethnographic study through in-depth interviews with informants, field observations, and documentation of plant species. The quantitative method used is recording how many people use the coloring plants and calculating the RFC. This study identifies various species of plants used as natural dyes and their utilization. A total of 53 plant species from 37 families have been identified and utilized as color producers in Kalibawang Sub-district. The most widely used plant parts are fruit (36%) and leaves (28%), the plant forms are herbs (49%) and trees (26%), the colors are red (28%) and green (15%), used to color food (49%), and drinks (42%). Most of these plants are intentionally planted (53%), but most of them are rarely used (43%), only a few are frequently used (26%), among the most important are turmeric (Curcuma longa L.) (RFC 0.891) for yellow color, and pandan (Pandanus amaryllifolius Roxb. ex Lindl.) (RFC 0.633), and green grass jelly (Cyclea barbata Miers) (RFC 0.613) for green color. The sustainability of several species needs attention because of their conservation status, namely Tectona grandis L.f. (EN), Coffea arabica L. (EN), and Cinnamomum verum J.Presl (VU). The dye extraction method usually uses water or other natural ingredients. This study shows that natural dyes have the potential to be further innovated. However, this traditional knowledge is in danger of being lost due to lifestyle changes and the lack of interest of the younger generation. Hence, it needs to increase public awareness of the potential of natural dyes as an alternative to synthetic dyes and to engage the community in this important issue.